Simulation of optical gain in AlGaN quantum wells - Kolle, S.; Römer, Friedhard; Cardinali, G.; Schultz, A.; Susilo, N.; Vidal, D. Hauer; Wernicke, T.; Kneissl, M.; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2023)
Simulations of optical gain in aluminum gallium nitride (AlGaN) quantum wells are extended to the high charge density regime required for achieving gain at 275 nm for UV laser diodes. Coulomb interaction is modeled using the 2nd Born approximation. We demonstrate good agreement with experimental data obtained through optical pumping, and predict gain spectra for electrical pumping.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aluminum gallium nitride; Optoelectronic devices; Quantum well lasers; Simulation